2018
DOI: 10.1128/jvi.00224-18
|View full text |Cite
|
Sign up to set email alerts
|

Aedes Anphevirus: an Insect-Specific Virus Distributed Worldwide in Aedes aegypti Mosquitoes That Has Complex Interplays with Wolbachia and Dengue Virus Infection in Cells

Abstract: Insect specific viruses (ISVs) of the yellow fever mosquito have been demonstrated to modulate transmission of arboviruses such as dengue virus (DENV) and West Nile virus by the mosquito. The diversity and composition of the virome of, however, remains poorly understood. In this study, we characterised Aedes anphevirus (AeAV), a negative-sense RNA virus from the order AeAV identified from cell lines were infectious to both and cells, but not to three mammalian cell lines. To understand the incidence and geneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 95 publications
4
66
0
Order By: Relevance
“…Note that our analysis was conducted on pools of mosquitoes, which limits the conclusions that can be drawn in this study versus an analysis conducted on individual mosquitoes and interviral dynamics. For example, although Anphevirus (described in our analyses) has been shown to reduce DENV titers in vitro during coinfections, further analysis performed using individual mosquitoes of this specific dynamic is necessary to fully determine whether Anphevirus coinfection (occurring singly or concomitantly with other ISVs) can mediate multigenerational dengue virus persistence in mosquitoes (12).…”
Section: Discussionmentioning
confidence: 99%
“…Note that our analysis was conducted on pools of mosquitoes, which limits the conclusions that can be drawn in this study versus an analysis conducted on individual mosquitoes and interviral dynamics. For example, although Anphevirus (described in our analyses) has been shown to reduce DENV titers in vitro during coinfections, further analysis performed using individual mosquitoes of this specific dynamic is necessary to fully determine whether Anphevirus coinfection (occurring singly or concomitantly with other ISVs) can mediate multigenerational dengue virus persistence in mosquitoes (12).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that dual viral infections in mosquito can alter viral infectivity (Fujita et al, 2018) and ISVs are more and more considered as potential disease control agents in vector populations (Guzman et al, 2018;Öhlund et al, 2019). Virus phenotypic restriction could be more complex as Parry and Asgari (2018) highlighted that restriction of Dengue virus replication in Ae.aegypti mosquitoes could be hindered by interactions between a novel ISV and the endosymbiotic bacterium Wolbachia pipientis. In contrast, Zhang et al (2017) pointed out that Cell fusing agent virus, another ISV, favor Dengue virus replication in Ae.aegypti cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that dual viral infections in mosquito can alter viral infectivity [47] and ISVs are more and more considered as potential disease control agents in vector populations [40,48]. Virus restriction phenotypic could be more complex as Parry and Asgari [49] highlighted that restriction of Dengue virus replication in Ae.aegypti mosquitoes could be hindered by interactions between Aedes anphevirus (AeAV) a novel ISV and the endosymbiotic bacterium Wolbachia pipientis. In contrast, Zhang et al [50] pointed out that Cell fusing agent virus, another ISV, favour Dengue virus replication in Ae.aegypti cell lines.…”
Section: Discussionmentioning
confidence: 99%